Analysis of Perceived Effects of Rainfall Variability on Rice Yield in Lokoja, Kogi State, Nigeria - Folorunsho, Joseph Olaniyi; Ajiwoju, Moses (ABUAD Journal of Social and Management Sciences, 2024)
This study analyzes the perceived effects of rainfall variability on rice production in Lokoja using data on rainfall and rice production from 2013 to 2022, and data on demographic and socio-economic characteristics of farmers as well as their perception on the effects of rainfall variability. The study was done using well-structured questionnaire administered in the study area to the 140 selected respondents, and the Statistical Package for the Social Sciences (SPSS) version 24 was utilized to analyze the data. Results showed that rainfall have significant effects on rice production with varied yield based on rainfall fluctuations in the amount of rainfall with as much rice production of about 4269 tonha-1 when precipitation was suitable between about 1250 - 1350mm, but when less than normal precipitation (<1250mm), it reduces the production yield to about 2361 tonha-1. Similarly, the results revealed that when the rainfall amount was highest, the total rice production was reduced, with cultivated areas having heavy rainfall resulting in flooding. Results further showed that on average 1282mm of rainfall produced 2693 tons of rice in the study years. About 44% of the respondents refuted early rainfall onset affecting rice production with months such as June, July, and September in some of the years with high rainfall intensity having adverse effects on rice farming, with 43% of the respondent noting that it limited the amount of land available for cultivation, while 26% noted that it reduces rice yield while the remaining 31% noted that it destroys rice stands.